Memory Layers in Architectural, Natural and Urban Heritage: The Case of İstanbul Bosphorus Area - Gülersoy, Nuran Zeren (ICONARCH International Congress of Architecture and Planning, 2017)
Natural and urban heritage of the Bosphorus with its ecological and cultural layers that reflect the environmental, social, spatial, and political meanings are the major elements of personal and collective memories and also the identity of Istanbul. However, in conditions of rapid urbanisation, cultural and natural values of the Bosphorus have been experiencing the pressures of the Metropolitan City of Istanbul since the 1970s in particular. Accordingly, emphasising the importance of the Bosphorus with its contribution to the cultural and natural values and urban heritage of Istanbul, the main aim of this study is to determine and evaluate the effects of the conservation and development decisions, on the memory layers of the city throughout its development history.